Drug-induced systemic lupus erythematosus after 7 years of treatment with carbamazepine - Pelizza, L.; De Luca, P.; La Pesa, et al., M. (Acta Biomedica Atenei Parmensis, 2006)
Aim of this work is to describe a late-onset of carbamazepine-induced systemic lupus erythematosus (SLE) in a 38-year-old female patient who had been treated with daily carbamazepine (CBZ) for 7 years because of a bipolar I disorder.When CBZ was discontinued, symptoms rapidly improved and antinuclear antibodies (ANA) disappeared. So far, only few cases have been reported of CBZ-induced SLE within months after the beginning of treatment. This is the second (first italian) case report in literature about CBZ-induced SLE with serological confirmation after years of treatment without previous side effects.